Effect of arbuscular mycorrhiza fungi on the growth, nutrient uptake, root infectivity and soil colonisation of rough lemon (Citrus jambhiri) seedlings - Chebet, DK; Wanzala, FK; Wamocho, LS (My University, 2022)
The effect of Arbuscular mycorrhiza (AM) fungi on growth, nutrient uptake and root infectivity was determined in Rough Lemon (Citrus jambhiri) seedlings raised under four phosphorus regimes in sand culture and also in sand/nitrosol sterile and unsterile conditions. Inoculation with AM fungi increased the plant height, leaf number and stem girth in relation to un-inoculated seedlings grown under equivalent P concentrations. An increase in plant height, leaf number and stem girth also occurred in both inoculated sterile and un-sterile sand/nitrosol media in relation to un-inoculated sterile and unsterile media. Arbuscular mycorrhiza also increased the leaf area and the root, leaf and stem fresh and dry weights and also caused an increase in the uptake of phosphorus and potassium in the leaf tissues. It also favoured mycorrhizal infectivity of roots and increased the root absorptive surface area. This study indicates that AM fungi improves the capacity of tropical fruit to absorb and utilize plant nutrients possibly by increasing the effective root surface area from which available form of nutrients are absorbed and also by increasing access of roots by bridging the depletion zones. Inoculating seedlings with arbuscular mycorrhizal fungi helps to alleviate the adverse effects of global warming and climate change. As a low cost technology, arbuscular mycorrhizal inoculation is recommended as part of the regular practise for incorporating into nursery media used for tropical fruit seedling propagation.
Keywords: Journal of Agronomy; Papaya; Phosphorus; Potassium; Passion fruit